Factors associated with all-cause mortality among patients initiating maintenance hemodialysis - Xiaojuan Wang; Bin Jiang; Mohamad Hafizi Abu Bakar; Xiaoli Ma; Manli Xu; Congjing Shi; Suning Fu (Medicine, 2026)
Survival outcomes among patients receiving maintenance hemodialysis (MHD) vary considerably across regions and healthcare settings. This study aimed to identify factors associated with all-cause mortality among patients initiating MHD at a county-level hospital in China. In this single-center retrospective cohort study, incident hemodialysis patients treated between 2016 and 2018 were followed until death, censoring, or December 31, 2021. The primary outcome was all-cause mortality. Baseline demographic, clinical, dialysis-related and laboratory variables were compared between patients who died and those who survived or were censored. Survival was estimated using Kaplan–Meier analysis, and factors associated with mortality were examined using multivariable Cox proportional hazards regression. A total of 144 patients were included, of whom 90 died during follow-up. The Kaplan–Meier estimated 1-, 2-, and 3-year survival rates were 73.6%, 56.9% and 46.0%, respectively. In the multivariable Cox model, older age was associated with higher all-cause mortality (hazard ratio [HR] = 1.036, 95% confidence interval (CI): 1.019–1.054, P < .001), as was diabetes mellitus (HR = 4.400, 95% CI: 1.894–10.223, P = .001). Compared with diabetic nephropathy, chronic glomerulonephritis was associated with lower mortality (HR = 0.258, 95% CI: 0.106–0.626, P = .003). Arteriovenous fistula as the initial vascular access (HR = 0.390, 95% CI: 0.233–0.653, P < .001) and higher maintenance dialysis frequency (HR = 0.532, 95% CI: 0.403–0.702, P < .001) were associated with reduced mortality. Older age, diabetes mellitus, DN, initial central venous catheter use, and lower maintenance dialysis frequency were associated with poorer survival among patients initiating MHD. These findings highlight the importance of early risk stratification, vascular access planning and optimization of dialysis delivery in incident hemodialysis care.